Implementation of Decision Making in the Public Sector in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2022)
In the organization, decision-making is based on the authority governed by the organization’s needs. Inaccuracies in decision-making regarding the forum, process, approach, and the decision results will reduce the power of cohesion between organization members in supporting the decision. This study aims to identify, review, evaluate, and interpret research related to the decision-making process in organizations. With the Systematic Literature Review approach pattern in journals that have been published from 2016 to 2021, the results show that current decision-making implementation research focuses on two topics and trends: supervision and the role of leaders. The method that is often used in research on the implementation of decision-making is a quantitative approach of 75% and a qualitative approach of 25%. The cause of the low performance of decision-making in the public sector is a leader who allows himself to be overwhelmed by doubts controlling his way of thinking and acting. Keywords: Systematic Literature Review, Implementation, Decision Making.